The correlation between types of posterior upper rotator cuff tears and intramuscular fat infiltration based on magnetic resonance imaging: A retrospective observational study - Yu, Xiao-Kun; Cao, Jia-Xi; Li, Lei; Guo, Wen-Bin; Zhang, Le; Li, Jin-Xing (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: This study investigated the correlation between types of posterior upper rotator cuff tears (RCTs) and intramuscular fat infiltration (FI) in magnetic resonance imaging (MRI). Methods: The shoulder joints of 50 adults with a full-thickness posterior upper RCT diagnosed by MRI, from January 2019 to December 2021, were retrospectively analyzed. The patients were divided into three groups according to tear type: 1) an L-shaped tear group; 2) a crescent/U-shaped tear group; 3) a complete tear group. The correlation among age, gender, tear range, trauma history, and the duration of clinical symptoms was analyzed. The MRI images were used by two musculoskeletal imaging physicians to evaluate the type and range of tears, the Goutallier grade of the supraspinatus and infraspinatus, and the correlations and reliability were analyzed. Results: Differences in the tear range (p < 0.001) and the Goutallier grade of the infraspinatus muscle (p = 0.036) among the L-shaped, crescent/U-shaped, and complete tear groups were statistically significant; however, differences in the Goutallier grade of the supraspinatus muscle was not statistically significant (p = 0.356). In the crescent/U-shaped tear group, age was significantly correlated with the Goutallier grade of the supraspinatus muscle (RS = 0.720, p = 0.029) and the infraspinatus muscle (RS = 0.713, p = 0.032). In the complete tear group, tear range was significantly correlated with the Goutallier grade of the supraspinatus muscle (RS = 0.801, p = 0.001) and the infraspinatus muscle (RS = 0.802, p = 0.001). The Goutallier grades of the supraspinatus muscle (kappa, 0.489) and the infraspinatus muscle (kappa, 0.424) presented with interobserver consistency. Conclusion: The type of posterior upper RCT correlates with the degree of FI. There is a positive correlation between the FI of crescent/U-shaped full-thickness RCTs and age. Additionally, the range of complete tears in the posterior upper RC has a positive correlation with FI.